Mildly compromised tetrahydrobiopterin cofactor biosynthesis due to Pts variants leads to unusual body fat distribution and abdominal obesity in mice - Korner, Germaine; Scherer, Tanja; Adamsen, Dea; Rebuffat, Alexander; Crabtree, Mark; Rassi, Anahita; Scavelli, Rossana; Homma, Daigo; Ledermann, Birgit; Konrad, Daniel; Ichinose, Hiroshi; Wolfrum, Christian; et al. (Journal of inherited metabolic disease, 2016)
Tetrahydrobiopterin (BH4) is an essential cofactor for the aromatic amino acid hydroxylases, alkylglycerol monooxygenase, and nitric oxide synthases (NOS). Inborn errors of BH4 metabolism lead to severe insufficiency of brain monoamine neurotransmitters while augmentation of BH4 by supplementation or stimulation of its biosynthesis is thought to ameliorate endothelial NOS (eNOS) dysfunction, to protect from (cardio-) vascular disease and/or prevent obesity and development of the metabolic syndrome. We have previously reported that homozygous knock-out mice for the 6-pyruvolytetrahydropterin synthase (PTPS; Pts-ko/ko) mice with no BH4 biosynthesis die after birth. Here we generated a Pts-knock-in (Pts-ki) allele expressing the murine PTPS-p.Arg15Cys with low residual activity (15 % of wild-type in vitro) and investigated homozygous (Pts-ki/ki) and compound heterozygous (Pts-ki/ko) mutants. All mice showed normal viability and depending on the severity of the Pts alleles exhibited up to 90 % reduction of PTPS activity concomitant with neopterin elevation and mild reduction of total biopterin while blood L-phenylalanine and brain monoamine neurotransmitters were unaffected. Yet, adult mutant mice with compromised PTPS activity (i.e., Pts-ki/ko, Pts-ki/ki or Pts-ko/wt) had increased body weight and elevated intra-abdominal fat. Comprehensive phenotyping of Pts-ki/ki mice revealed alterations in energy metabolism with proportionally higher fat content but lower lean mass, and increased blood glucose and cholesterol. Transcriptome analysis indicated changes in glucose and lipid metabolism. Furthermore, differentially expressed genes associated with obesity, weight loss, hepatic steatosis, and insulin sensitivity were consistent with the observed phenotypic alterations. We conclude that reduced PTPS activity concomitant with mildly compromised BH4-biosynthesis leads to abnormal body fat distribution and abdominal obesity at least in mice. This study associates a novel single gene mutation with monogenic forms of obesity.